Are Zirconia Implant Abutments Safe and Predictable in Posterior Regions? A Systematic Review and Meta-Analysis - Jose Vechiato-Filho, Aljomar [UNESP]; Pesqueira, Aldieris Alves [UNESP]; De Souza, Grace M.; Santos, Daniela Micheline dos [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Goiato, Marcelo Coelho [UNESP] (Quintessence Publishing Co Inc, 2016)
Purpose: This systematic review aimed to evaluate whether the survival rate and predictability of zirconia abutments are similar to those of titanium abutments for single implant crowns in the posterior area. Materials and Methods: A systematic search of two databases (Medline/PubMed and Cochrane Library) was performed by two independent reviewers for articles published between January 2004 and July 2014. The electronic search was complemented by a hand search of the following journals from the same period: Journal of Periodontology, Clinical Oral Implants Research, International Journal of Prosthodontics, and International Journal of Oral and Maxillofacial Implants. Studies included were published in English, evaluated single implant crowns, and performed a mean observation a 1 year. Any disagreement between the reviewers was solved by means of a discussion. Forest plot and funnel were used to compare zirconia and titanium abutments. Results: The search strategy identified 669 studies. Of these, 11 studies were included and only 6 studies were selected for meta-analysis. The pooled results for fixed implant single crowns in posterior areas showed a 5-year success rate of 99.3% for zirconia abutments and 99.57% for titanium abutments. There was no statistical difference regarding veneer failure (P = .26). The pooled results of these studies showed that the mean bone loss was 0.38 +/- 0.87 mm for zirconia and 0.2 +/- 0.13 mm for titanium abutments. Conclusion: The use of zirconia abutments for single implant-fixed crowns in posterior regions is questionable due to the absence of long-term data. The short-term results of zirconia abutments regarding mechanical and biologic responses are similar to titanium abutments. Caution when using zirconia abutments in posterior regions is necessary until further clinical evidence shows favorable long-term results.